An Analysis of Environmental Themed Poetry Writing Skills among Eighth Grade Students at SMPN 1 Patimpeng - Alizah, Nur; Firana, Firna; Hardiansyah, Muhammad; Dewi, Anita Candra (The Future of Education Journal, 2026)
This study aims to describe students' ability to write environmental-themed poetry, outline the creative process, and identify obstacles faced. The research method used was descriptive with a mixed approach, namely qualitative and quantitative. The subjects were six eighth-grade students at SMPN 1 Patimpeng. Data collection techniques included observation of the learning process, poetry writing tests, and in-depth interviews. The results showed that the average student activity was in the Good category (3.57), with the highest scores in the aspects of readiness and environmental observation, and the lowest scores in the aspects of idea development and language use. Based on the test results, students' abilities were divided into three categories: one student (16.67%) in the Good category, three students (50%) in the Average category, and two students (33.33%) in the Poor category. The main obstacles identified were difficulty in determining titles, constructing beautiful diction, and selecting appropriate figures of speech. Strategies used by students to overcome these difficulties included re-observing the environment, searching for references online, and discussing with teachers and friends. It was concluded that despite the students' high enthusiasm, their mastery of poetic techniques still needs to be improved through intensive practice.